2008
DOI: 10.1038/sj.sc.3102168
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic vs non-traumatic spinal cord lesions: comparison of neurological and functional outcome after in-patient rehabilitation

Abstract: Study design: Retrospective comparative study of 2 years duration. Objectives: To compare neurological and functional outcome and length of stay of persons with traumatic vs non-traumatic spinal cord lesion (SCL) after in-patient rehabilitation. Setting: Neurological rehabilitation department of a tertiary research center in Bangalore, Karnataka, India. Methods: Seventy-six in-patients with spinal cord lesion: traumatic (38 patients, M/F ¼ 34:4) and non-traumatic (38 patients, M/F ¼ 16:22) were admitted for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
5
33
2
4
Order By: Relevance
“…Consistent with other studies, 7,18,19 NTSCI patients had significantly fewer days spent in inpatient rehabilitation compared to TSCI and had higher FIM scores upon discharge. Both NTSCI and TSCI had high outpatient health care utilization patterns; however, there were differences in the types of health care used.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with other studies, 7,18,19 NTSCI patients had significantly fewer days spent in inpatient rehabilitation compared to TSCI and had higher FIM scores upon discharge. Both NTSCI and TSCI had high outpatient health care utilization patterns; however, there were differences in the types of health care used.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have reported mean ages for NTSCI ranging from 31 to 61 years with a relatively even sex distribution. 3,18,19 The majority of the NTSCI sample had paraplegia compared with the TSCI group which is also consistent with previous work. 6,7 It is noteworthy that 42% of the NTSCI sample did not have a level of injury specified whereas only 14.3% were nonspecified for TSCI.…”
Section: Socio-demographic and Clinical Characteristicssupporting
confidence: 90%
See 1 more Smart Citation
“…McKinley et al attributed this difference to the fact that non-traumatic patients were more often motor incomplete (ASIA C and D) than their traumatic counterparts. Similar results have been reported by Ones et al, 9 while Gupta et al 10 did not find any difference between the two populations at admission. Unfortunately in both these studies a correction for the covariant effect of age and neurological impairment is lacking, so their results are difficult to interpret.…”
Section: Discussionsupporting
confidence: 88%
“…However, in spite of the high incidence of non-traumatic lesions, which is considered to vary between 25 and 80% of the total admission for spinal cord injuries, there are still few studies on the influence of different etiologies (namely traumatic vs non-traumatic) on SCL outcome; [5][6][7][8][9][10][11] this is probably due to the different features of the two populations with regard to age, lesion severity and lesion to admission time (LTA), which are wellknown prognostic factors: 5 therefore, the two groups of patients are poorly comparable.…”
Section: Introductionmentioning
confidence: 99%